Favus In A Non-endemic Area - Gupata L K; Bansal N K; Kuldeep C M; Surana S S; Mehta P; Jasuja K; Sharma A (Wolters Kluwer Medknow Publications, 2002)
Favus, although endemic in the Kashmir valley, is rarely reported form other parts of India. We report two cases of favus from rural Udaipur, Rajasthan, because of its rarity in a non- endemic zone. Both the patients had scutula and cicatricial alopecia, characteristic of scales. Culture on Sabouraudâ€s dextrose agar grew Trichophyton schoenleinii in both the cases.